The management of acute venous thromboembolism in clinical practice - Cohen, Alexander T.; Gitt, Anselm K.; Bauersachs, Rupert; Fronk, Eva-Maria; Laeis, Petra; Mismetti, Patrick; Monreal, Manuel; Willich, Stefan N.; Bramlage, Peter; Agnelli, Giancarlo; the PREFER in VTE Scientific Steering Committee and the PREFER in VTE Investigators; on behalf of (Thrombosis and Haemostasis, 2017)
Venous thromboembolism (VTE) is a significant cause of morbidity and mortality in Europe. Data from real-world registries are necessary, as clinical trials do not represent the full spectrum of VTE patients seen in clinical practice. We aimed to document the epidemiology, management and outcomes of VTE using data from a large, observational database. PREFER in VTE was an international, non-interventional disease registry conducted between January 2013 and July 2015 in primary and secondary care across seven European countries. Consecutive patients with acute VTE were documented and followed up over 12 months. PREFER in VTE included 3,455 patients with a mean age of 60.8 ± 17.0 years. Overall, 53.0% were male. The majority of patients were assessed in the hospital setting as inpatients or outpatients (78.5%). The diagnosis was deep-vein thrombosis (DVT) in 59.5% and pulmonary embolism (PE) in 40.5%. The most common comorbidities were the various types of cardiovascular disease (excluding hypertension; 45.5%), hypertension (42.3%) and dyslipidaemia (21.1%). Following the index VTE, a large proportion of patients received initial therapy with heparin (73.2%), almost half received a vitamin K antagonist (48.7%) and nearly a quarter received a DOAC (24.5%). Almost a quarter of all presentations were for recurrent VTE, with >80% of previous episodes having occurred more than 12 months prior to baseline. In conclusion, PREFER in VTE has provided contemporary insights into VTE patients and their real-world management, including their baseline characteristics, risk factors, disease history, symptoms and signs, initial therapy and outcomes.
Keywords: Venous thromboembolism; anticoagulation; registry; direct oral anticoagulants; vitamin K antagonists